(untitled) (MAUSAM, 1970)
The differential equation for cup and vane anemometers was set up on analogue computers and the responses of the instruments studied for sinusoidal and random types of wind speed variation. The effects of both static and dynamic friction have been taken into accouut. The results show a large exaggeration of mean indicated wind speeds, a large attenuation in the gust amplitudes and a distortion in gust shapes.